PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI SEKOLAH DASAR - HENNI, SETI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Problems faced by at observation in the class of IV SDN 18 Gunung Tuleh obtained by picture that study still centrally at teacher, less varying applied study him mode, so that make student less optimum in the opinion. If teacher raise question about items studied,  most student unable to reply him answer later, then student in doing duty often expect aid of this research. Support for describe to make-up of the learn result student in PKn study with using mode of PBL in class of IV SDN 18 Gunung Tuleh Sub-Province of West Pasaman. This research use approach qualitative and quantitative with type research of class action, covering planning phase, execution, and perception of reflection. Result of obtained research at meeting of one cycle of one percentage RPP is 60,71%, meeting of two cycle of one is 75% and 96,43% at cycle of two. Activity learn at meeting of one cycle is I 61,11%, meeting of two cycle of one is 77,78% and at cycle of two 91,67%. Student activity meeting of one cycle of one is 58,33%, meeting of two cycle of one is 75% and 88,89% at cycle of two. Mean Class result of learning student at cycle of one tired of number 71,8 completely klasikal 56%. At cycle of two class mean go up to become 80 complete with of classical is 88%. The conclusion of this research that mode applying  of problem learning based can improve result learn PKn student in class of IV SDN 18 Gunung Tuleh Sub-Province of West Pasaman.     Kata kunci : hasil belajar, model, problem based learning